(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article reveals the essence of national values in developing a culture of tolerance in society. It has highlighted that maintaining a society from decline, and maintaining stability, is only associated with tolerance as a criterion of an open society. Ideas such as interethnic harmony and tolerance, loving people, respecting them, satisfying their material and spiritual needs, ensuring their freedom and rights as individuals, the role of peace in the formation of tolerance, spiritual maturity and compatibility aspects of tolerance have been deeply analyzed.